3-D presentation of calibration data of a perimetry eye tracker - Doytchinov, Simeon; Henning, Günter; Mueller, Winifred (Digital Journal of Ophthalmology, 1997)
A calibration method for eye movements monitoring in standard and objective static perimeters is described. Current static perimeters require the subjects to maintain steady fixation during the entire examination. By implementing eye tracking methods adopted for perimetry, automatic fixation monitoring is possible during perimetrical test. Successful fixation monitoring allows conditional eye movements. An important issue in designing a fixation monitoring unit is the method of initial eye tracker calibration. The aim of this study is to demonstrate an alternative way to present the eye tracker calibration data in a three dimensional coordinate system. The resulting figure allows precise and fast calibration data assessment. The calibration method is based on an analysis of the distance between the images of the corneal reflection and the pupil center for calibration points at specific locations. The method provides an accuracy of 1deg. in calculating the fixation point for +/- 20 deg. eccentricities of the line-of-sight relative to the center of the perimeter by using 8 calibration points and could be expanded to any other view field by using more calibration points. The calibration procedure can be completed in under 1 minute. The required time depends on the patient’s ability to concentrate. The model is subject specific and once calculated it can be used in multiple recording sessions. Based on the perimeter’s polar coordinate system this model is particularly suitable for implementation in perimetry, however, it can easily be adopted in eye testing equipment with different setups.